Normalized representation of the equations of active multiport networks on the basis of projective geometry - Penin, Alexandru (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2011)

(untitled)
To interpret the mutual influence of loads of active multiport networks, some methods of projective geometry are used. The application of the projective coordinates gives the possibility to derive an equation of the network in a normalized or relative form as well as to define the scales for the currents and conductivity of the loads. This approach makes it possible to identify parameters of the regime and to compare the regimes of different multiports. The given approach is applicable to the analysis of «flowed» form processes of different physical nature. The obtained results can be useful in the educational purposes. This new mathematical apparatus for the circuit theory is widely applied in other areas of science.